CONVERGENCE COMMUNICATION MODEL DALAM UPAYA PENGELOLAAN TANAMAN PANGAN DI ACEH BARAT - Asgha, Ashabul Yamin; Amri, Saiful; Nisa, Uswatun (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
West Aceh is one of the districts in Aceh Province that prioritizes the agricultural sector in food crops. This can be seen from the number of food crop agricultural commodities in West Aceh that number 561 groups or reach 44% of the total number of other commodities. This research aims to describe the communication resource management carried out by the West Aceh district government using a convergence model approach. The method used is descriptive qualitative with data collection techniques, namely interviews, observation and documentation studies. The informants for this research were 10 people from the West Aceh Food Crops and Horticulture Department, PERHIPTANI, as well as farming communities. The data analysis techniques used are data collection, reduction, data presentation and drawing conclusions. The results of the research show that the communication resource management efforts that have been carried out by the West Aceh Agricultural Food Crops and Horticulture Service as the implementer are to prepare planning programs according to farmers' needs in increasing rice yields, such as by prioritizing farmer group training. Furthermore, by preparing human resources (HR) that are appropriate to their expertise and field of work, this aims to make it easier to achieve goals. Implementation of program development is carried out directly, both with training and outreach aimed at farmer groups, however the involvement and participation of farmer groups is still relatively low.